Mathematics achievement emotions: Global trend, emotional treatment, and directions for future research - Suparman Suparman; Dadang Juandi (Al-Jabar)
Background: The development of studies related to achievement emotions in mathematics learning has been increasingly grown in two last decades. Achievement emotions is one of significant predictors for students’ mathematics achievement. Nevertheless, to date no publications have been found that particularly review studies regarding mathematics achievement emotions.